“Did you have a good weekend?” A week-level diary study examining the relationship between weekend recovery and weekday performance - van Wyngaarden, Georgia (Organisational Psychology, 2022)
Sufficient rest breaks are needed for optimal performance in traditional workplaces, but it is unclear how working with a loosely structured work schedule impacts recovery. Students have temporal flexibility and serve as a good proxy for all groups who work unstructured work schedules. Since most students and employees use the weekend to recover, this study investigated the relationship between recovery experiences (i.e., psychological detachment, relaxation, and mastery) over the weekend and the state of being recovered on the following Monday. Further, the relationship between the state of being recovered on Monday and weekday performance indicators (i.e., task performance and personal initiative) was investigated. Data was collected over three consecutive weeks from a cohort of first-year university students (N = 106) using a quantitative diary study design. This study administered seven surveys (i.e., a personal data survey once, a pre-weekend survey three times, and a postweekend survey three times). After three weeks, 66 participants (N = 66) had completed all the surveys at the person level, yielding 148 matched observations at the week-level. Multilevel modelling showed that weekend relaxation positively predicted the state of being recovered on Monday. Weekend psychological detachment and weekend mastery experiences did not predict the state of being recovered on Monday, and the state of being recovered did not predict weekly personal initiative or weekly task performance. The theoretical and practical implications of this study are presented, as are limitations and suggestions for future research.